2015
DOI: 10.1016/j.jconrel.2015.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Enema ion compositions for enhancing colorectal drug delivery

Abstract: Delivering drugs to the colorectum by enema has advantages for treating or preventing both local and systemic diseases. However, the properties of the enema itself are not typically exploited for improving drug delivery. Sodium ions are actively pumped out of the lumen of the colon, which is followed by osmotically-driven water absorption, so we hypothesized that this natural mechanism could be exploited to drive nanoparticles and drugs to the colorectal tissue surface. Here, we report that sodium-based, absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…We previously found that, similar to what was observed in the human colorectum [25], sodium-driven water absorption continued to occur in the mouse colorectum for enema vehicles above the conventional isoosmolar point and up to 400–500 mOsm/kg [23]. Thus, our isotonic vehicle contained 2.5 mg/mL 2-PMPA dissolved in 1.32% w/v sodium chloride and titrated to pH 7.0 ± 0.1 using 3.5 M NaOH (final osmolality of 450 ± 5 mOsm/kg).…”
Section: Methodsmentioning
confidence: 68%
See 2 more Smart Citations
“…We previously found that, similar to what was observed in the human colorectum [25], sodium-driven water absorption continued to occur in the mouse colorectum for enema vehicles above the conventional isoosmolar point and up to 400–500 mOsm/kg [23]. Thus, our isotonic vehicle contained 2.5 mg/mL 2-PMPA dissolved in 1.32% w/v sodium chloride and titrated to pH 7.0 ± 0.1 using 3.5 M NaOH (final osmolality of 450 ± 5 mOsm/kg).…”
Section: Methodsmentioning
confidence: 68%
“…Having previously observed that hypotonic enema solutions provide improved colorectal drug distribution and absorption [23,30], we first tested whether administering 2-PMPA hypotonically would lead to increased colorectal tissue levels in mice with TNBS-induced colitis. Indeed, we found that at 30 mins after enema administration, the hypotonic vehicle provided a 1.6-fold increase in colorectal tissue 2-PMPA levels compared to the isotonic vehicle (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of prior rectal cleansing and fecal washout, enema spreading and drug delivery will be less homogenous in space (along the canal) and in time (in relation to enema application and expulsion). Future modeling of this more complex process will be informed by imaging studies of vehicle distribution along the rectum[21,34]. …”
Section: Discussionmentioning
confidence: 99%
“…Ensign et al demonstrated that by using hypotonic solution as delivery vehicle, muco-inert (i.e. densely PEGylated) nanoparticles were able to rapidly penetrate the luminal mucus layer and reached the immediate surfaces of vaginal [315] and colorectal [316] epithelium in vivo . However, the effect and safety of this approach is yet to be established for delivery of inhaled therapeutics, including gene vectors.…”
Section: Strategies To Overcome the Barriers To Inhaled Gene Therapymentioning
confidence: 99%